Aplikasi “Golek Tukang” untuk Pencarian Jasa Perbaikan Rumah di Daerah Surabaya Berbasis Android - Andreas Endrahadi Wijaksono; Henry Novianus Palit; Anita Nathania Purbowo (Jurnal Infra, 2019)
In the reality of life today, many people have smartphones connected to the internet. This condition causes an increase in information needs through gadgets. One of them is to search for home improvement services / builders online through the application on the smartphone. But in the Surabaya area to find a handyman, they still use a manual system with the principle of finding information on builders through the website or by word of mouth so that the people of Surabaya do not meet the appropriate home improvement needs.With that problem, the Android Golek Tukang application will be created to find home repair services. The feature provided in the